2008
DOI: 10.1038/nrn2398
|View full text |Cite
|
Sign up to set email alerts
|

Can the immune system be harnessed to repair the CNS?

Abstract: Experimental and clinical data have demonstrated that activating the immune system in the CNS can be destructive. However, other studies have shown that enhancing an immune response can be therapeutic, and several clinical trials have been initiated with the aim of boosting immune responses in the CNS of individuals with spinal cord injury, multiple sclerosis and Alzheimer's disease. Here, we evaluate the controversies in the field and discuss the remaining scientific challenges that are associated with enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
208
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(214 citation statements)
references
References 287 publications
4
208
0
2
Order By: Relevance
“…However, inflammatory responses are complex, and benefits of inflammation to the CNS are increasingly being appreciated (Schwartz and Yoles, 2006;Popovich and Longbrake, 2008). Indeed, in support of our finding for a beneficial role for neutrophil recruitment, others have documented more oxidative stress within the injured cord in the absence of neutrophils (de Castro et al, 2004).…”
Section: Discussionsupporting
confidence: 69%
“…However, inflammatory responses are complex, and benefits of inflammation to the CNS are increasingly being appreciated (Schwartz and Yoles, 2006;Popovich and Longbrake, 2008). Indeed, in support of our finding for a beneficial role for neutrophil recruitment, others have documented more oxidative stress within the injured cord in the absence of neutrophils (de Castro et al, 2004).…”
Section: Discussionsupporting
confidence: 69%
“…8 Recent studies have demonstrated that sCD95L promotes an autoimmune reaction; 21 however, it is still unclear whether autoimmune reactions are beneficial or if a 'protective autoimmunity' exists. 22 In other words, there is not enough evidence to suggest that mCD95L is associated with neurological damage and sCD95L is associated with beneficial processes following SCI. Nevertheless, this is an interesting question and we hope that researchers will pursue it in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…2). In CNS injury, the upregulation and activation of MMPs, a known component of the P2Y 2 R signaling pathway [38], can be either beneficial or detrimental depending on the length of time after the injury, the profile of the inflammatory cells at the injury site, and the substrates present [201]. During neuroinflammation, astrocytes undergo morphological and functional changes (i.e., reactive gliosis) characterized by hypertrophy, proliferation, upregulation of the intermediate filament protein glial fibrillary acidic protein, accumulation of activated glial cells around plaques, adhesion of cells to Aβ peptides, internalization and degradation of Aβ peptides by activated glial cells, expression of proteinases required for Aβ peptide catabolism, production of arachidonic acid and related proinflammatory substances in the vicinity of plaques, and regulation of regenerative processes in the brain [202][203][204][205][206].…”
Section: P2y 2 Rs In Cns Inflammationmentioning
confidence: 99%